2017
DOI: 10.1186/s13046-017-0631-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived xenograft in zebrafish embryos: a new platform for translational research in gastric cancer

Abstract: BackgroundGastric cancer (GC) is among the most commonly cancer occurred in Asian, especially in China. With its high heterogeneity and few of validated drug targets, GC remains to be one of the most under explored areas of precision medicine. In this study, we aimed to establish an in vivo patient-derived xenograft (PDX) model based on zebrafish (Danio rerio) embryos, allowing for a rapid analysis of the angiogenic and invasive potentials, as well as a fast drug sensitivity testing.MethodsTwo human gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 44 publications
(51 reference statements)
5
84
0
Order By: Relevance
“…Regarding zebrafish larval xenografts using patient-derived samples, few studies have been published so far (see Table S1). Nevertheless, these studies show promising results and the reliability of the zPDX model to establish different cancer types, as it is able to overcome some of the disadvantages of the murine PDXs such as the time required to develop an assay, as well as number of cells needed for implantation [106,115,[128][129][130][131].…”
Section: Zebrafish Patient-derived (Zpdx)-avatarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding zebrafish larval xenografts using patient-derived samples, few studies have been published so far (see Table S1). Nevertheless, these studies show promising results and the reliability of the zPDX model to establish different cancer types, as it is able to overcome some of the disadvantages of the murine PDXs such as the time required to develop an assay, as well as number of cells needed for implantation [106,115,[128][129][130][131].…”
Section: Zebrafish Patient-derived (Zpdx)-avatarsmentioning
confidence: 99%
“…Subsequent work from Wu J.Q. et al [129] showed that patient-derived gastric zPDXs were able to metastasize and recruit vessels into the tumor mass. A retrospective correlation with the patient clinical outcome was shown only for one patient.…”
Section: Zebrafish Patient-derived (Zpdx)-avatarsmentioning
confidence: 99%
“…Upon localised or haematogenous engraftment of cancer cells, zebrafish xenografts allow qualitative and quantitative assessment of tumour burden and tumour-microenvironment interaction, representing a powerful pre-clinical model to unravel cancer mechanisms and to develop new therapeutic strategies [61] . In particular, alongside murine models, the use of PDXs in zebrafish has the potential to be used in personalised medicine [63][64][65][66] , with the advantage of requiring less tumour material and shorter times for the monitoring of tumour development [57] . Several studies have shown that the combined use of zebrafish and murine models paves the way towards important insights to elucidate the biology of metastatic cancers and the development of new treatments [67][68][69][70][71] .…”
Section: Zebrafish Xenograft As a Model To Study Cancermentioning
confidence: 99%
“…xenograft (zPDX) models have also been generated by transplanting hundreds of cells from human tumor tissue with a high success rate [3,[5][6][7][8]. The relative stemness and immature immune environment of zebrafish larvae represent proper conditions for the growth of human cancer cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the mouse xenograft model, the transparent zebrafish larvae xenograft model offers the speed and intuitiveness for studies on the cellular resolution level with relatively large samples [1,7,8], which would contribute to the study of tumor biology. Thus, developing reliable zebrafish…”
mentioning
confidence: 99%